Do consumers like food product innovation? An analysis of willingness to pay for innovative food attributes. Issue 6 (13th March 2019) - Nazzaro, Concetta; Lerro, Marco; Stanco, Marcello; Marotta, Giuseppe
Abstract : Purpose: The purpose of this paper is to investigate consumer's acceptance toward product innovation in the agri-food sector, uncovering consumers' characteristics able to encourage food innovation acceptance. Design/methodology/approach: The analysis was carried out by administering a web-based structured questionnaire to a convenient sample of 443 Italian consumers. The study relies on consumers' willingness to pay (WTP) to assess consumers' acceptance toward the innovative product, while the Food-Related Lifestyle scale was applied to perform a cluster analysis aiming at detecting the attitude of consumers toward innovations in a traditional food. Findings: The study findings showed a clear openness of consumers toward product innovation. Indeed, consumers' WTP for the innovative product was far higher than the traditional one. Further, two out of three consumers' groups detected (i.e. pro-innovation and rational adopters) exhibit a broad correlation between the innovative product attributes and consumers' psychographics characteristics, revealing the existence of a large number of potential consumers. Originality/value: The contribution of the paper to the current literature is twofold. First, it focused on an emerging topic for the agri-food sector (i.e. product innovation) whereby research works are still scarce. Second, product innovation was addressed toward a traditional food that is mostly reluctant to innovation due to consumers' resistance and skepticism.